Analysis of Government’s Performance Accountability Report Preparation at Layouts, Building Structure, and Housing Department of Padang City Government Period 2014-2017 - Lexy Putri Ananta; Rimi G Mais (Indonesian Journal of Business, Accounting and Management (IJBAM), 2018)
Abstract— This research analyzes how the Local Government of Padang, especially at Layouts, Building Structure, and Housing Department (TRTB Department) of Padang City preparing Government Performance Accountability Report (LAKIP) in the period 2014 to 2017 from the standpoint of preparation, distribution internal and external agencies, also the process for evaluating and implications for government policy in the future. The analysis is done by looking at the implementation of the mechanism of regulation conformity with the rule set, which is the reference was the Head of the Decree No. 239 LAN Regulations of 2003 and The Minister of State For Administrative Reform and Bureaucratic Reform No. 29 of 2010. This research uses a case study as a research approach to dig deeper information. Data collection techniques used was literature study, document analysis, and interviews. The primary data used was interviews with the main source of research namely the Head of TRTB Department of Padang City Mr. Ir. Dian [2] Fakri, M.Sp. as well as secondary data obtained from various sources such as accounting standards, government regulations, LAKIP documents of TRTB Department of Padang City, and also the official website of the relevant institutions. The results of the research prove that the preparation of the LAKIP of TRTB Department of Padang City has been carried out in accordance with the laws and regulations, the distribution system of the LAKIP is in accordance with applicable regulations according to the LAKIP writing guidelines, the LAKIP value of TRTB Department of Padang City is already quite good but there is no reward and punishment system, and the benefits of LAKIP are as a consideration for granting or defense of positions the head departments.